(untitled) (Bangladesh Journal of Anatomy, 2015)
Context: The major duodenal papilla is one of the most fascinating papilla present at the duodenum attracting many gastroenterologists as they do endoscopic retrograde cholangiopancreatiography (ERCP) for diagnosis and treatment purpose of many diseases. Most of the textbooks of Anatomy describe that the summit of major duodenal papilla is situated posteromedially in the descending part of duodenum. Henceforth the present study was undertaken in 70 human duodenums to observe the location of major duodenal papilla. Materials & Methods: A cross-sectional observational study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka from July 2010 to June 2011. Seventy postmortem human duodenums were collected from unclaimed dead bodies that were under examination in the morgue of department of Forensic Medicine and the department of Anatomy of Dhaka Medical College, Dhaka. Location of major duodenal papilla was observed and recorded. Results: The location of major duodenal papilla was observed in the medial wall of second part of duodenum in 78.6% specimens, in the posteromedial wall of second part in 15.7% cases and in the posteromedial wall of the junction between second and third part in 4.3% and absent in 1.4% duodenum. Conclusion: The location of major duodenal papilla varies in position. DOI: http://dx.doi.org/10.3329/bja.v12i1.22614 Bangladesh Journal of Anatomy, January 2014, Vol. 12 No. 1 pp 22-24